A requiem for BMI in the clinical setting. Issue 5 (September 2017) - Gonzalez, Maria Cristina; Correia, Maria Isabel T.D.; Heymsfield, Steven B.
Abstract : Purpose of review: Quetelet reported in the nineteenth century that body weight varies across adults with the square of height. Quetelet's index, now known as BMI, is accepted by most health organizations as a first-level measure of body fat and as a screening tool for diagnosing excess adiposity. Modern imaging methods now, however, indicate that BMI has limited predictive value for estimating body fat and lean mass at the individual level. The use of BMI as a measure of body composition in the clinical setting should therefore be challenged. Recent findings: Recent studies enrolling cancer and surgical patients reported discrepant outcomes when BMI was used as a body composition surrogate. Sarcopenia, loss of muscle mass and function, which affects the elderly and those with chronic and acute diseases, is not accurately diagnosed with BMI. The distribution of adipose tissue is not characterized by BMI, specific measures of which have greater predictive value for metabolic impairments and clinical outcomes. Summary: BMI, as the traditional tool for assessing malnutrition and obesity, is not appropriate to accurately differentiate between important body weight components and therefore should not be used for making clinically important decisions at the individual patient level.